Study of some variables which influence the labelling iodoantipyrine 131I - Suñer, Antonio A.; Bianco de Salas, Gladis N.; Mitta, Aldo Eduardo Antonio (1970)
Fil: Suñer, Antonio A. Comisión Nacional de Energía Atómica; Argentina